TERMISUL E INFORMÁTICA: CAMINHO PERCORRIDO E HORIZONTE A ALCANÇAR - Maciel, Anna Maria Becker (Organon, 2011)
This paper reports on the quest for the interface between Terminology, Informaticsand the Termisul Project. Three landmarks highlight the account, DOS, Windows, and Internet.They characterize the steps of a team of linguists towards the computerized era. As far as thetechnology advanced, their perception of digital resources changed from being mereoperational help in data management to representing sophisticated tools assisting research andeventually to the demand of cooperative work with computer scientists. The difficulties of theearly stages encountered in the path tread are remembered. The meaningful results of theefforts taken are described. The challenges of the ongoing research work are outlined.